Effect of Short-Term Steroid Therapy on Early Recurrence During the Blanking Period After Catheter Ablation of Atrial Fibrillation. (December 2015) - Kim, Yoo Ri; Nam, Gi-Byoung; Han, Seungbong; Kim, Sung-Hwan; Kim, Ki-Hun; Lee, Sulhee; Kim, Jun; Choi, Kee-Joon; Kim, You-Ho
Abstract : Background—: Early recurrence (ER) of atrial tachyarrhythmias during the first 3 months (blanking period) after atrial fibrillation ablation can be highly symptomatic, often requiring emergency treatment. Short-term steroid therapy may suppress ER during the blanking period. Methods and Results—: We prospectively enrolled 138 patients who were randomly assigned to 2 groups (steroid group and control group). An intravenous bolus of 0.5 mg/kg of methylprednisolone for 2 days followed by 12 mg daily of oral methylprednisolone for 4 days was given to the steroid group patients. The primary end point was ER during the blanking period (3 months post ablation). During the blanking period, 51 of the 138 (37.0%) patients experienced ER after atrial fibrillation ablation. The steroid group had a lower rate of ER than the control group (15/64 [23.4%] versus 36/74 [48.6%], P =0.003). There was no difference between the 2 groups about late recurrence during a 24-month follow-up (log-rank test, P =0.918). In a multivariate analysis, short-term steroid therapy was independently associated with a lower rate of ER during the blanking period (adjusted OR, 0.45; 95% confidence interval, 0.25–0.83; P =0.01). Conclusions—: Periprocedural short-term moderate intensity steroid therapy reduces ER (≈3 months) after catheter ablation of atrial fibrillation. It is not effective in preventing late (3≈24 m) atrial fibrillation recurrence. Clinical Trial Registration—: URL:www.who.int/ictrp ; Unique identifier: KCT0000107. Abstract : Supplemental Digital Content is available in the text.